FACTORS INFLUENCING THE INCOME OF RICE FARMING IN GAMPONG BLANG RIEK, KUTAMAKMUR DISTRICT, ACEH UTARA DISTRICT - Cut Iklillah; Mawardati Mawardati; Suryadi Suryadi (LPPM Universitas Malikussaleh - Indonesia, 2023)
The research was conducted in Blang Riek Village, Kutamakmur District in August 2022. This study aims to analyze the income off paddy rice farming in Blang Riek Villange, Kutamakmur District, North Aceh Regency and to analyze the factors that influence the income of Lowland Rice Farming in Blang Riek Village, Kutamakmur Disrict, North Aceh District.This research used a purposive sampling method and direct interviews were carried out to obtain data using a questionnaire. The number of samples in this study were farmers who carried out rice farming in Blang Riek Village, Kutamakmur District, with a total sample of 33 people. This analysis data using SPSS software. The results of this study indicate that the variable selling price and production simultaneously have a significant and positive relationship to the income of lowland rice farmers. While partially the selling price has no significant effect and is positively related to income. While partially production has a significant and positive relationship to farmer income. Keywords: income, selling price, production.